"God is my doctor": mindfulness meditation/prayer as a spiritual well-being coping strategy for Jamaican school principals to manage their work-related stress and anxiety. Issue 4 (7th July 2020) - Walker, Annette Rosemarie
Abstract : Purpose: This article explores Jamaican secondary school principals' use of mindfulness meditation as a spiritual well-being strategy to manage their work-related stress and anxiety. Design/methodology/approach: The author used qualitative semi-structured interviews to collect the data from 12 Jamaican secondary school principals working in schools supporting rural, urban and inner-city school communities. Thematic coding of the analyzed data was used to understand how principals deal with their work-related stress and anxiety. Findings: The findings indicate that Jamaican school principals are experiencing work-related stress and anxiety as a result of work intensification, and use mindfulness meditation/prayer as a spiritual coping strategy. The data indicate that principals' primary source of support is their spiritual belief – faith in God and mindfulness meditation/prayer – when dealing with issues related to well-being. Originality/value: This article explores the use of mindfulness meditation as a non-secular coping strategy, and focuses on an understudied area of educational administration research: Jamaican school principals' well-being. The findings can help inform future education and health policy around occupational health and well-being for professionals, and lay the foundation for greater studies on principal well-being in Jamaican and the Caribbean more generally.